PEMODELAN KLASIFIKASI TERUMBU BERBASIS GEOMORFOLOGI DAN PEMANFAATAN SUMBERDAYA IKAN KARANG - Wikanti Asriningrum; Budy Wiryawan; Domu Simbolon; Iwan Gunawan (Buletin PSP, 2007)
Coral reef is one of important economical value natural resources which is grow better in tropical region. Indonesia as a tropical country consists of 17.508 islands and 70% territory covered by sea, in which the shallow waters around the islands, is a place for coral reef to grow. Since the biophysical characteristic information of coral reef is essential for regional marine planning, this research aims to study the satellite remote sensing data processing for geomorphologic analysis of small islands, volcanic, coral, and atoll, and reef landform in order to arrange a geomorphology-based reef classification model. Domination, uniformity, and variety analysis of coral fish is conducted to find out the relationship between small island, reef and coral fish habitat. From remote sensing data processing model, multispectral fusion results obtained are 245 channel combinations for volcanic islands, 257 for coral islands, 237 for atoll islands, and 124 for coral reefs. Spectral enhancement is autoclip and spatial enhancement is high pass sharpen 2. Multispatial fusion enhances small island morphology but not enhances for coral reefs. Geomorphology-based reefs classification model divides reef into oceanic reef and shelf reef. More detailed classification for oceanic reef is divided into fringing reef, barrier reef, and atoll. While shelf reef used in the study area is lagoonal platform reef. This classification, combined with ecological-based coral reef classification, is used to identify life reef, dead reef, and sand in the certain reef landform.